Local problems, local solutions: improving tuberculosis control at the district level in Malawi - Kelly Paul M. (The World Health Organization, 2001)
OBJECTIVE: To examine the causes of a low cure rate at the district level of a tuberculosis (TB) control programme and to formulate, implement, and evaluate an intervention to improve the situation. METHODS: The study setting was Mzuzu (population 60 000), where the annual smear-positive pulmonary TB incidence was 160 per 100 000 and the human immunodeficiency virus (HIV) seroprevalence was 67% among TB patients. There is one TB treatment unit, but several other organizations are involved with TB control. An examination of case-holding activities was carried out, potential areas for improvement were identified, and interventions performed. FINDINGS: In 1990-91, the cure rate was 24% among smear-positive cases (29% among survivors to end of treatment). Problems identified included a fragmented TB control programme; inadequate training and supervision; suboptimal recording of patients? addresses; and nonadherence to national TB control programme protocols. These problems were addressed, and in 1992-93 the cure rate rose to 68% (relative risk (RR) = 2.85 (95% confidence interval (CI) = 1.63, 4.96)) and to 92% among survivors to the end of treatment (RR = 3.12 (95% CI = 1.84, 5.29)). High cure rates are therefore achievable despite high HIV prevalence. CONCLUSIONS: Simple, inexpensive, local programmatic interventions can dramatically improve TB case holding. This study demonstrates the need for evaluation, training, and supervision at all levels of the programme.